RANCANG BANGUN SISTEM INFORMASI PENGELOLAAN WISATA PULAU RANOH BERBASIS WEBSITE: RANCANG BANGUN SISTEM INFORMASI PENGELOLAAN WISATA PULAU RANOH BERBASIS WEBSITE - Nurjaya, Nurjaya; Elisa, Erlin (LPPM Universitas Putera Batam, 2023)
The purpose of making the Design and Development of a Website-Based Ranoh Island Tourism Management Information System is to promote and facilitate booking of tour packages on Ranoh Island. Web-based visual information system is a system consisting of text and graphic images. It is these factors that make these tours interesting and make bookings easy. In addition, the Website-Based Ranoh Island Tourism Management Information System is a system that contains complete information for tourists and can be found at any time. This support cannot be separated from the research process design and technology. This study aims to design a Website-Based Ranoh Island Tourism Management Information System as a source of information for viewing and ordering tourist attractions and other facilities on Ranoh Island. The Website-Based Ranoh Island Tourism Management Information System was developed using the PHP programming language and data stored in a database using MySQL to optimize system and database performance. The Google Maps API is one of the features of this information system that can be used to add maps to websites using JavaScript. The result of the design is a web tourism information system which should be a way to promote tourism in the city of Batam, so that through this web design it is hoped that there will be a similar system to create better services. and more complete than existing services.